Agronomic and genetic diversity in intermediate wheatgrass (Thinopyrum intermedium). (28th October 2016) - Jensen, Kevin B.; Yan, Xuebing; Larson, Steve R.; Wang, Richard R.‐C.; Robins, Joseph G.
Abstract: Intermediate wheatgrass [ Thinopyrum intermedium (Host) Barkworth & D. R. Dewey] plant introductions (PI) have played a critical role in the development of improved intermediate wheatgrass cultivars. The objective of this study was to characterize a large number of intermediate wheatgrass populations over its native range for dry matter yield (DMY), crude protein (CP), in vitro true digestibility (IVTD), neutral detergent fibre (NDF), and rhizome development and genetic diversity and structure to identify superior populations and possible geographical regions in which to collect. Analysis of molecular variance using 643 AFLP bands partitioned 31% of the total genetic variation among these populations with 69% variance detected within populations. Bayesian cluster analysis identified two large groups designated as Asian and European under K  = 2. In general, European accessions had greater DMY than did Asian accessions. Observed trends were towards greater CP values in populations with Asian ancestry. Selection index values above zero were observed in populations with European ancestry, and the exception was the late‐maturing (208 days to bloom) populations with Asian ancestry. Plant populations 383 551, 383 561, 401 161, 401 173, 440 021, 578 692 (cv. Tegmar) and 598 740 had rhizome scores greater than 7.0. Despite significant differences detected between populations (ΦST  = 0.3136; P < 0.001), there was strong indication of admixed co‐ancestry or possible gene flow between K  = 2–9 models.